2014
DOI: 10.1111/gwao.12064
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment of Women Working as Room Attendants within 5‐Star Hotels

Abstract: Given the gendered power relations and the isolated nature of women hotel room attendants' working environments, guest‐initiated sexual harassment experienced by room attendants is a significant, under‐investigated problem. This study of women attendants' experiences of sexual harassment was conducted in 5‐star hotels located on the Gold Coast — a notable tourism destination — of Queensland, Australia. Adopting a socialist–feminist critical theory epistemological perspective, the study used a qualitative const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
108
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 64 publications
12
108
2
1
Order By: Relevance
“…Participants' reports of gendered dependency situations were also in line with Gettman and Gelfand's () description of ‘power perspectives': sexual harassment that arises from men's economic power over women, and which enables sexual exploitation and coercion. Although these findings accord with previous studies in the service industries (Kensbock et al, ; Seymour, ), positional power did not appear to protect women from sexual harassment as suggested by McLaughlin et al (). In the creative industries this is possibly due to non‐standard and precarious patterns of work that feature discontinuous skills acquisition, strong competition for work and networked recruitment.…”
Section: Discussionsupporting
confidence: 90%
“…Participants' reports of gendered dependency situations were also in line with Gettman and Gelfand's () description of ‘power perspectives': sexual harassment that arises from men's economic power over women, and which enables sexual exploitation and coercion. Although these findings accord with previous studies in the service industries (Kensbock et al, ; Seymour, ), positional power did not appear to protect women from sexual harassment as suggested by McLaughlin et al (). In the creative industries this is possibly due to non‐standard and precarious patterns of work that feature discontinuous skills acquisition, strong competition for work and networked recruitment.…”
Section: Discussionsupporting
confidence: 90%
“…Although early studies on harassment show that some hospitality organisations trained staff to flirt (Gilbert et al, 1998), and in a recent study, participants complained of sexualised hospitality uniforms (Kensbock et al, 2015), evidence that management explicitly sexualises labour is scarce, and employees may have a different view of organisational expectations than management intends (e.g. Jiang et al, 2015).…”
Section: The Role Of Managers In the Sexualisation Of Labourmentioning
confidence: 97%
“…However, more experienced employees are better at distinguishing between their work and personal selves (Yagil, 2008), so are less vulnerable. In a study of cleaning staff in Australian luxury hotels, Kensbock et al (2015) observed that young, inexperienced workers, were acutely vulnerable to sexual harassment, as they lacked experience in dealing with difficult people and situations.…”
Section: Influences On Sexual Harassment In the Workplacementioning
confidence: 99%
See 1 more Smart Citation
“…Without a delineated organizational ‘pecking order’ (Höpfl, ) in hotels, there would be no clear career structure for ambitious individuals. The findings suggested an apparent paradox, as experienced and skilled housekeeping workers — at the very bottom of the occupational class hierarchy in hotels (Kensbock et al , ) — exhibited their agency by celebrating their long‐term careers in these lowest positions. Rather than being passive recipients of organizational processes (Choo and Ferree, ), workers paid ‘the tax’ of lower wages to achieve a better work/life balance at a particular point in time.…”
Section: Discussionmentioning
confidence: 99%